Cardiac Resynchronisation with Conduction System Pacing - Fatima M Ezzeddine; Isaac G Leon; Yong-Mei Cha (Arrhythmia & Electrophysiology Review)
To date, biventricular pacing (BiVP) has been the standard pacing modality for cardiac resynchronisation therapy. However, it is non-physiological, with the activation spreading between the left ventricular epicardium and right ventricular endocardium. Up to one-third of patients with heart failure who are eligible for cardiac resynchronisation therapy do not derive benefit from BiVP. Conduction system pacing (CSP), which includes His bundle pacing and left bundle branch area pacing, has emerged as an alternative to BiVP for cardiac resynchronisation. There is mounting evidence supporting the benefits of CSP in achieving synchronous ventricular activation and repolarisation. The aim of this review is to summarise the current options and outcomes of CSP when used for cardiac resynchronisation in patients with heart failure.